Master techniques in surgery - Nussbaum, Michael S. (Master techniques in surgery, 2013)
Master Techniques in Surgery: Gastric Surgery is a volume in a new series that presents common and advanced procedures in the major subspecialties of general surgery. The series is overseen by Josef E. Fischer, MD, editor of the classic two-volume reference Mastery of Surgery. Master Techniques in Surgery is written by acknowledged master surgeons, emphasizes surgical procedures, and is lavishly illustrated with original full-color drawings. The contributors fully explain their preferred techniques in step-by-step, thoroughly illustrated detail, assess indications and contraindications, offer guidelines on preoperative planning, and discuss outcomes, complications, and follow-up. This volume covers surgical procedures of the stomach and includes sections on procedures for ulcer disease, procedures for neoplastic disease, operations for postgastrectomy syndromes, bariatric operations, and other gastric operations. A companion website will offer the fully searchable text and procedural videos.